How the Gospels became history: Jesus and Mediterranean myths - Litwa, M. David (Synkrisis, 2019)
A compelling comparison of the gospels and Greco-Roman mythology which shows that the gospels were not perceived as myths, but as historical records Did the early Christians believe their myths? Like most ancient--and modern--people, early Christians made efforts to present their myths in the most believable ways. In this eye-opening work, M. David Litwa explores how and why what later became the four canonical gospels take on a historical cast that remains vitally important for many Christians today. Offering an in-depth comparison with other Greco-Roman stories that have been shaped to seem like history, Litwa shows how the evangelists responded to the pressures of Greco-Roman literary culture by using well-known historiographical tropes such as the mention of famous rulers and kings, geographical notices, the introduction of eyewitnesses, vivid presentation, alternative reports, and so on. In this way, the evangelists deliberately shaped myths about Jesus into historical discourse to maximize their believability for ancient audiences